Learning experience and relationships among learners in online Recovery College courses: An exploratory qualitative study - Sauvageau, Anick; Bellemare, Julie; Briand, Catherine (Journal of Recovery in Mental Health)

(untitled) (Ontario Shores Centre for Mental Health Sciences, 2025)
Introduction: Recovery Colleges (RC) are community-based learning centers. They offer courses in mental health, well-being and recovery. RC courses are co-constructed and co-facilitated by two trainers with complementary knowledge. Learners come from diverse backgrounds ensuring a variety of expertise and experiences. Studies have demonstrated the benefits of RC courses for learners. The mechanisms of action specific to RC explains the benefits. Studies about the mechanisms of action of RC show the importance of the social environment of RC. The Centre d'apprentissage Santé et Rétablissement (CASR) is a Canadian French-language RC offering free online courses to the public. Objectives: The study aims to answer two research question: 1- How do learners of CASR’s online courses describe their learning experience? 2- How do learners of CASR’s online courses describe the relationships they experienced? Methods: An exploratory qualitative study consisting of ten individual interviews followed by a thematic analysis was conducted. Results: Participants describe their learning experiences in terms of the characteristics of the CASR course space: inclusive and benevolent learning space; connected, supportive, and egalitarian space for interaction; collaborative and co-constructed knowledge space. Participants describe the relationships in terms of: equality; respect and non-judgment; recognition and belonging; collaboration and mutual support. Conclusion: The results confirm the existence of mechanisms of action in CASR courses like those identified in previous studies. The learning context of the CASR prompts some participants to prioritize their personal roles over their professional roles during courses. By exposing their vulnerability, they show humility and encounter equal relationships.